Dialektika Islam dan Budaya: Dakwah Kultural Nahdlatul Ulama - Librianti, Eka Octalia Indah (STAI AL-FALAH CICALENGKA, 2019)
The intersection between culture and religion in Indonesia is one of the interesting discourses to be examined more deeply. This paper aims to explore how the contiguity of Islam and the local culture of Indonesia raises the concept of the preaching of the Nahdlatul Ulama Culture. The spread of Islam in the archipelago has shown accommodation that is so strong against the local traditions of the local community. This shows that the character of Indonesian Islam is capable of dialogue with tradition and culture. Nahdlatul Ulama as one of the largest Islamic organizations in Indonesia in carrying out its mission to try to adopt da'wah that harmonizes Islam and local culture. This paper tries to examine the cultural preaching of the Nahdlatul Ulama and the relations between Islam and local culture. Cultural da'wah is da'wah that considers all forms of culture that are developing in society. Cultural propaganda carried out by Nahdlatul Ulama is a da'wah approach in dealing with heterogeneous societies of culture. Islam has an important role in facing cultural transformation. The process of Islamic dialogue with the traditions of the community can be realized with cultural systems and mechanisms in the face of local negotiations. From the display illustrates that in reality, Islam came into contact with local teachings (traditions) so as to form new formulations about Islam and the local culture of Islam. Keywords: cultural preaching, Nahdlatul Ulama, dialectics. Abstrak Persinggungan antara budaya dan agama di Indonesia menjadi salah satu diskursus yang menarik untuk ditelisik lebih mendalam. Tulisan ini bertujuan untuk mengeksplorasi bagaimana persentuhan agama Islam dengan kebudayaan lokal Indonesia yang memunculkan konsep dakwah Kultural Nahdlatul Ulama. Penyebaran Islam di Nusantara telah menunjukan akomodasi yang begitu kuat terhadap tradisi lokal masyarakat setempat. Hal ini menunjukkan bahwa karakter Islam Indonesia mampu berdialog dengan tradisi dan budaya. Nahdlatul Ulama sebagai salah satu organisasi Islam terbesar di Indonesia dalam menjalankan misi dakwahnya mencoba mengadopsi dakwah yang menyelaraskan antara Islam dan budaya lokal. Tulisan ini mencoba mengkaji dakwah kultural Nahdlatul Ulama serta relasi antara Islam dan budaya lokal. Dakwah kultural merupakan dakwah yang mempertimbangkan segala bentuk budaya yang tengah berkembang di masyarakat. Dakwah kultural yang dilakukan oleh Nahdlatul Ulama merupakan pendekatan dakwah dalam menghadapi masyarakat yang heterogen kebudayaan. Islam memiliki peran penting dalam menghadapi transformasi budaya. Proses dialog Islam dengan tradisi masyarakat dapat diwujudkan dengan sistem dan mekanisme kultural dalam menghadapi negosiasi lokal. Dari tampilan tersebut menggambarkan bahwa pada realitasnya, Islam bersentuhan dengan ajaran (tradisi) lokal sehingga membentuk formulasi baru tentang Islam dan budaya lokal Islam. Kata Kunci : dakwah kultural, Nahdlatul Ulama, dialektika